PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN POWERPOINT INTERAKTIF TERINTEGRASI GEOGEBRA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Erika Dwi Anggraeni; Kriswandani Kriswandani; Yenny Deswita; Siti Robithoh (LPPM Universitas Bina Bangsa, 2023)
This Best Practice aims to determine the effect of using the Problem Based Learning (PBL) Model assisted by interactive PowerPoint integrated with GeoGebra on students' mathematical problem solving abilities. The subjects of this study were 32 students in class VIII H of SMP Negeri 4 Salatiga for the 2022/2023 academic year. The design used in this best practice uses the One-Group Pretest-Posttest with data analysis techniques using the Wilcoxon signed rank test. Data collection techniques include essay tests, observation of learning implementation, and student response questionnaires. Best Practice results show that the Problem Based Learning (PBL) model assisted by GeoGebra integrated interactive PowerPoint has an effect on students' mathematical problem solving abilities. This can be seen from the results of the Wilcoxon test with a value of Sig.=0.00<0.05 which indicates that there is a difference in the average pretest and posttest results where the mean value after being given the GeoGebra interactive PowerPoint-assisted PBL model is better than the average value before being given this learning model. In addition, the results of learning implementation were 95.59%, and student responses to GeoGebra integrated interactive PowerPoint learning media were 94.14%.